DETERMINING THE RELATIONSHIP BETWEEN TEMPERATURE AND TUNING FORK FREQUENCY CHANGES WITH POLYNOMIAL REGRESSION MODELLING - Hasan, Aly; Natalisanto, Adrianus Inu; Zarkasi, Ahmad (Universitas Mataram, 2024)
A tuning fork is a unique tool made of metal and shaped like the letter U, with one handle. Tuning forks can produce specific frequencies; usually, the value is written on the handle. This study aims to investigate the relationship between temperature and changes in tuning fork frequency and model it using polynomial regression. This research uses laboratory experiments with tuning forks with 341.3 Hz, 426.5 Hz, and 512 Hz frequencies. The temperature on the tuning fork varies from 30C to 220C with a difference of 10C. From the results of the study adjusted R-Square values sequentially 0.94745, 0.99565, and 0.97721, which stated the relationship between temperature and frequency changes. The Adjusted R-Square value close to 1 means that changes in temperature on the tuning fork greatly influence changes in the frequency produced by the tuning fork, and the polynomial regression model used is very suitable.